Identification of a variable number of tandem repeats polymorphism and characterization of LEF-1 response elements in the promoter of the IDO1 gene. - Marion Soichot; Benjamin Hennart; Alaa Al Saabi; Audrey Leloire; Philippe Froguel; Claire Levy-Marchal; Odile Poulain-Godefroy; Delphine Allorge (PLoS ONE)
Background Indoleamine 2,3-dioxygenase (IDO) catalyzes the first and rate-limiting step of the kynurenine pathway that is an important component of immunomodulatory and neuromodulatory processes. The IDO1 gene is highly inducible by IFN-γ and TNF-α through interaction with cis-acting regulatory elements of the promoter region. Accordingly, functional polymorphisms in the IDO1 promoter could partly explain the interindividual variability in IDO expression that has been previously documented. Methodology/principal findings A PCR-sequencing strategy, applied to DNA samples from healthy Caucasians, allowed us to identify a VNTR polymorphism in the IDO1 promoter, which correlates significantly with serum tryptophan concentration, controlled partially by IDO activity, in female subjects, but not in males. Although this VNTR does not appear to affect basal or cytokine-induced promoter activity in gene reporter assays, it contains novel cis-acting elements. Three putative LEF-1 binding sites, one being located within the VNTR repeat motif, were predicted in silico and confirmed by chromatin immunoprecipitation. Overexpression of LEF-1 in luciferase assays confirmed an interaction between LEF-1 and the predicted transcription factor binding sites, and modification of the LEF-1 core sequence within the VNTR repeat motif, by site-directed mutagenesis, resulted in an increase in promoter activity. Conclusions/significance The identification of a VNTR in the IDO1 promoter revealed a cis-acting element interacting with the most downstream factor of the Wnt signaling pathway, suggesting novel mechanisms of regulation of IDO1 expression. These data offer new insights, and suggest further studies, into the role of IDO in various pathological conditions, particularly in cancer where IDO and the Wnt pathway are strongly dysregulated.